Neoechinulin A as a Promising SARS-CoV-2 Mpro Inhibitor: In Vitro and In Silico Study Showing the Ability of Simulations in Discerning Active from Inactive Enzyme Inhibitors - Hani A. Alhadrami; Gaia Burgio; Bathini Thissera; Raha Orfali; Suzan E. Jiffri; Mohammed Yaseen; Ahmed M. Sayed; Mostafa E. Rateb (Marine Drugs, 2022)
The COVID-19 pandemic and its continuing emerging variants emphasize the need to discover appropriate treatment, where vaccines alone have failed to show complete protection against the new variants of the virus. Therefore, treatment of the infected cases is critical. This paper discusses the bio-guided isolation of three indole diketopiperazine alkaloids, neoechinulin A (1), echinulin (2), and eurocristatine (3), from the Red Sea-derived Aspergillus fumigatus MR2012. Neoechinulin A (1) exhibited a potent inhibitory effect against SARS-CoV-2 Mpro with IC50 value of 0.47 μM, which is comparable to the reference standard GC376. Despite the structural similarity between the three compounds, only 1 showed a promising effect. The mechanism of inhibition is discussed in light of a series of extensive molecular docking, classical and steered molecular dynamics simulation experiments. This paper sheds light on indole diketopiperazine alkaloids as a potential structural motif against SARS-CoV-2 Mpro. Additionally, it highlights the potential of different molecular docking and molecular dynamics simulation approaches in the discrimination between active and inactive structurally related Mpro inhibitors.